Childhood maltreatment and personality disorders in patients with a major depressive disorder: A comparative study between France and Togo. (October 2015) - Kounou, Kossi B.; Dogbe Foli, Ayoko A.; Djassoa, G.; Amétépé, Léonard K.; Rieu, J.; Mathur, A.; Biyong, I.; Schmitt, L.
Few studies have examined the association between childhood maltreatment (CM) and personality disorders (PDs) in adulthood in two different cultural contexts, including sub-Saharan Africa. The aims of this study were to compare the frequency of CM between patients in treatment in France and Togo for a major depressive disorder (MDD), to explore the link between CM and PDs, and to examine the mediating effect of personality dimensions in the pathway from CM to PDs in 150 participants (75 in each country). The 28-item Childhood Trauma Questionnaire, the International Personality Item Pool, and the Personality Diagnostic Questionnaire (PDQ-4+) were used to assess CM, personality dimensions, and PDs respectively. Togolese participants reported sexual and physical abuse (PA) and emotional and physical neglect significantly more frequently than French participants. In Togo, severe PA was associated with schizoid, antisocial, narcissistic, obsessive-compulsive, depressive, and negativist PDs whereas in France, PA was only linked to paranoid PD. In Togo, emotional instability partly mediated the relationship between CM and PDs while in France, no personality dimension appeared to mediate this link. Our results support the hypothesis that CM is more common in low-income countries and suggest that the links between CM and PDs are influenced by social environment.